Using pharmacists to improve risk stratification and management of stage 3A chronic kidney disease: a feasibility study. Issue 1 (December 2016) - Chang, Alex; Evans, Michael; Yule, Christina; Bohn, Larissa; Young, Amanda; Lewis, Meredith; Graboski, Elisabeth; Gerdy, Bethany; Ehmann, William; Brady, Jonathan; Lawrence, Leah; Antunes, Natacha; et al.
Abstract Background Measurement of albuminuria to stratify risk in chronic kidney disease (CKD) is not done universally in the primary care setting despite recommendation in KDIGO (Kidney Disease Improving Global Outcomes) guidelines. Pharmacist medication therapy management (MTM) may be helpful in improving CKD risk stratification and management. Methods We conducted a pragmatic, cluster-randomized trial using seven primary care clinic sites in the Geisinger Health System to evaluate the feasibility of pharmacist MTM in patients with estimated glomerular filtration rate (eGFR) 45–59 ml/min/1.73 m2 and uncontrolled blood pressure (≥150/85 mmHg). In the three pharmacist MTM sites, pharmacists were instructed to follow a protocol aimed to improve adherence to KDIGO guidelines on testing for proteinuria and lipids, and statin and blood pressure medical therapy. In the four control clinics, patients received usual care. The primary outcome was proteinuria screening over a follow-up of 1 year. A telephone survey was administered to physicians, pharmacists, and patients in the pharmacist MTM arm at the end of the trial. Results Baseline characteristics were similar between pharmacist MTM (n = 24) and control (n = 23) patients, although pharmacist MTM patients tended to be younger (64 vs. 71 y;p = 0.06) and less likely to have diabetes (17 % vs. 35 %;p = 0.2) or baseline proteinuria screening (41.7 % vs. 60.9 %, p = 0.2). Mean eGFR was 54 ml/min/1.73 m2 in both groups. The pharmacist MTM intervention did not significantly improve total proteinuria screening at the population level (OR 2.6, 95 % CI: 0.5–14.0;p = 0.3). However, it tended to increase screening of previously unscreened patients (78.6 % in the pharmacist MTM group compared to 33.3 % in the control group; OR 7.3, 95 % CI: 0.96–56.3;p = 0.05). In general, the intervention was well-received by patients, pharmacists, and providers, who agreed that pharmacists could play an important role in CKD management. A few patients contacted the research team to express anxiety about having a CKD diagnosis without prior knowledge. Conclusions Pharmacist MTM may be useful in improving risk stratification and management of CKD in the primary care setting, although implementation requires ongoing education and multidisciplinary collaboration and careful communication regarding CKD diagnosis. Future studies are needed to establish the effectiveness of pharmacist MTM on slowing CKD progression and improvement in cardiovascular outcomes. Trial registration ClinicalTrials.gov, NCT02208674 Registered August 1, 2014, first patient enrolled September 30, 2014